The Evolution of Consumer Behavior in the Age of Information: An Analytical Review - I Gede Putu Suardana (Vifada Management and Digital Business, 2025)
This analytical review investigates the evolution of consumer behavior in the digital age, aiming to explore the impact of technological advancements on market dynamics and consumer preferences. Employing a comprehensive literature review, the study examines key themes and findings in consumer behavior, mainly focusing on the influence of digital platforms, big data analytics, and emerging technologies. The research design synthesizes existing studies and empirical evidence, shedding light on the transformative role of augmented reality, mobile devices, and social media in reshaping consumer-brand interactions and purchasing behaviors. The findings highlight a significant paradigm shift in consumer preferences and decision-making processes, driven by increased access to information, personalized marketing approaches, and consumer empowerment. Ethical considerations surrounding targeted advertising, consumer surveillance, and online misinformation are also discussed, emphasizing the importance of transparency and regulatory compliance in fostering consumer trust and brand integrity. The implications of these findings extend to businesses seeking to navigate the complexities of the digital landscape, emphasizing the need for strategic adaptation, ethical conduct, and consumer-centric approaches in driving sustained success in the digital era.